Effect of thermal characteristics on the chemical quality of real-brine treatment through hydrophilic fiber-based low-grade heat-powered humidification-dehumidification process. (15th April 2023) - Santosh, Ravichandran; Lee, Ho-Saeng; Ji, Ho; Kim, Young-Deuk
Highlights: High-salinity brine is treated with low-grade heat-powered fiber-based HDH process. Thermal characteristic influence on brine treatment chemical quality is explored. Preheating brine influences its ionic mobility aiding in better freshwater quality. Air post-heating reduces humidity ratio resulting in lower freshwater productivity. Single-stage HDH reduces pH, Na +, Cl −, and toxic B by ∼63, 99.9, 99.9, and 99.7%. Abstract: Considering the increasing demand for desalination plants and their byproduct brine, this study investigated a humidification-dehumidification (HDH) system for treating membrane distillation-generated real high-salinity brine using low-grade heat (45–70 ℃) to explore its feasibility for sustainable energy-efficient minimal liquid discharge. A novel super-hydrophilic fabric was adopted for accelerated humidification, and its impact on brine droplet miscarriage characteristics was evaluated. The influence of the operating fluid thermal properties (cycle 1: air preheating; cycle 2: air and brine dual-fluid preheating; and cycle 3: air post-heating after humidification) on the brine treatment efficiency, energy consumption, and chemical quality of freshwater produced was analyzed in detail to establish their characteristic nexus. It was identified that, during humidification, increasing the brine temperature (up to 55 ℃) influenced its ionic mobility, thereby promoting efficient separation of the salts/minerals and contributing to achieving better freshwater quality. Furthermore, although cycle 3 exhibited improved system thermal efficiency (gained output ratio equal to 1.77), its non-preheated air contributed to a negative effect of the reduced humidity ratio (∼17 g/kg), leading to a lower freshwater productivity of 67% than that of cycle 2 (29 g/kg and 70%). The present study also illustrates a novel effect of evaporative deposition occurring due to air-water interaction on the fabric humidifier surface, with an exploration of its effect on reducing freshwater chemical quality. The freshwater generated from optimum thermal cycle 2 exhibited reduced pH (by ∼63%), sodium (99.9%), chloride (99.9%), toxic boron (99.7%), and other chemical contaminants, thereby satisfying the major international water reuse standards. Graphical abstract: Image, graphical abstract